The Impact of an Online English Language Newspapers-Based Program on Enhancing EFL Critical Reading of Secondary Stage Students - Hammad, Marwa Abdel-Fattah; Qoura, Aly Abdelsamea; Gohar, Rehab Hamadtuh (جامعة المنصورة - كلية التربية, 2023)
لقد أجريت هذه الدراسة بهدف تحديد مدى فاعلية استخدام الصحف الإلكترونية الإنجليزية لتطوير مهارة القراءة الناقدة لدى طلاب المرحلة الثانوية. اعتمدت هذه الدراسة على التصميم التجريبي لتحقيق هذا الهدف، تم استخدام أداتين: (١) قائمة مهارات القراءة الناقدة (٢) اختبار مهارات القراءة الناقدة. وقد كانت عينة الدراسة تتكون من ٦٠ طالبة من الصف الأول الثانوي بمعهد فتيات بهواش الثانوي والذي تم تقسيمها إلى مجموعتين احدهما المجموعة التجريبية (35) طالبة يتم تدريبهم من خلال أنشطة الصحف الإلكترونية عبر الإنترنت والمجموعة الأخرى المجموعة الضابطة (٣٠) طالبة يتم تدريسهم بالطريقة التقليدية (تدريس وجها لوجه). أشارت النتائج إلى وجود فروق ذو دلالة إحصائية بين متوسط درجات الاختبار البعدين المجموعتين لصالح لمجموعة التجريبية. بالإضافة إلى وجود فروق ذات دلالة إحصائية بين متوسط الدرجات الاختبار القبلي والبعدي للمجموعة التجريبية لصالح الاختبار البعدي. قدمت الدراسة الحالية دليلاً واضحاً على أن استخدام الصحف الإلكترونية الإنجليزية كاستراتيجية نشطة وفعالة في تعزيز مهارة القراءة الناقدة لدى طلاب لصف الأول الثانوي. This research investigated the effectiveness of using an online newspapers-based program to develop first year secondary stage students’ EFL critical reading. The participants of the research were (60) first year Al-Azhar secondary stage students at Bahwash Secondary Institutes for Girls, Menofia, Egypt. To collect data, the researcher used two instruments; a critical reading skills checklist and an EFL critical reading skills test. The researcher taught both groups: the experimental group was taught through the online newspapers program, while the control group was taught through the regular method of teaching. Research results revealed that there were statistically significant differences between the mean score of the experimental group and the control group students in the EFL critical reading skills test. Moreover, the effect size of the online newspapers program was found to be high. Therefore, this research recommended using online newspapers in teaching the four skills of the English language at different educational stages.
Keywords: الصحف الإلكترونية -- القراءة النقدية -- اللغة الإنجليزية -- طلبة المرحلة الثانوية